Core–Shell Structure Trimetallic Sulfide@N-Doped Carbon Composites as Anodes for Enhanced Lithium-Ion Storage Performance - Xiuyan Li; Liangxing Zhu; Chenyu Yang; Yinan Wang; Shaonan Gu; Guowei Zhou (Molecules, 2023)
The high specific capacity of transition metal sulfides (TMSs) opens up a promising new development direction for lithium-ion batteries with high energy storage. However, the poor conductivity and serious volume expansion during charge and discharge hinder their further development. In this work, trimetallic sulfide Zn–Co–Fe–S@nitrogen-doped carbon (Zn–Co–Fe–S@N–C) polyhedron composite with a core–shell structure is synthesized through a simple self-template method using ZnCoFe–ZIF as precursor, followed by a dopamine surface polymerization process and sulfidation during high-temperature calcination. The obvious space between the internal core and the external shell of the Zn–Co–Fe–S@N–C composites can effectively alleviate the volume expansion and shorten the diffusion path of Li ions during charge and discharge cycles. The nitrogen-doped carbon shell not only significantly improves the electrical conductivity of the material, but also strengthens the structural stability of the material. The synergistic effect between polymetallic sulfides improves the electrochemical reactivity. When used as an anode in lithium-ion batteries (LIBs), the prepared Zn–Co–Fe–S@N–C composite exhibits a high specific capacity retention (966.6 mA h g−1 after 100 cycles at current rate of 100 mA g−1) and good cyclic stability (499.17 mA h g−1 after 120 cycles at current rate of 2000 mA g−1).